Catalytic Enantioselective Arylboration of Alkenylarenes. (14th December 2016) - Logan, Kaitlyn M.; Brown, M. Kevin
Abstract: A method for the catalytic enantioselective arylboration of alkenylarenes is disclosed. The reaction leads to the formation of 1, 1‐diarylalkanes that also incorporate an additional pinacol boronic ester which can be easily transformed to a variety of groups. The products are formed with excellent diastereoselectivities and enantioselectivities. Abstract : Einbauen und umwandeln : Die Titelreaktion liefert 1, 1‐Diarylalkane und führt gleichzeitig einen Pinakolboronsäureester ein, der leicht in eine Vielzahl funktioneller Gruppen umgewandelt werden kann. Die Produkte werden mit exzellenten Diastereo‐ und Enantioselektivitäten gebildet.